Development and Prospects of Halide Perovskite Single Crystal Films. (5th January 2022) - Gao, Wenxiu; Zhang, Zhuolei; Xu, Rukai; Chan, Emory M.; Yuan, Guoliang; Liu, Jun‐Ming
Abstract: Halide perovskite single crystal (HPSC) films have demonstrated extraordinary performance in solar cells, photodetectors, and lighting applications, owing to the high carrier mobility, long carrier diffusion length, tunable bandgap, and large light absorption coefficients of these materials. Here, the recent development of the major HPSC thin films is reviewed systematically, including MAPbI3, α‐FAPbI3, MAPbBr3, CsPbBr3, with special emphasis on different classes of fabrication methods and thin‐film characteristics. Finally, the conclusion and prospects in this field are discussed in detail. It is anticipated that the HPSC thin films will lead to a compelling future for the rising electronic applications. Abstract : Halide perovskite single crystal (HPSC) films attract wide attention due to the extraordinary performance such as high carrier mobility, long carrier diffusion length, and tunable bandgap. The representative fabrication methods and characteristics, as well as the applications of typical HPSC thin films, including MAPbI3, α‐FAPbI3, MAPbBr3, CsPbBr3, etc., are systematically reviewed. The prospects are also discussed at the end.